The role of service quality and knowledge sharing on customer loyalty café bang ciaat in Palangka Raya city - Noorjaya Nahan; Vivy Kristinae (Jurnal Mantik, 2023)
Research in the field of Marketing focuses on Service Marketing to increase Customer Loyalty. This research is based on the Dynamic Capability theory which indicates that a business unit to be able to survive must be evaluated and make business strategies that are relevant to the dynamics of business change, such as maintaining service quality and building business community relationships with knowledge sharing. The research was conducted at the Bang Ciaat café in Palangka Raya City with 100 consumers as a benchmark and analyzed using the SPSS 22 statistical program. The results prove that the important role of service quality and knowledge sharing is to increase customer loyalty, which is 63.7%. The implications of the results can be a reference for Bang Ciaat café business actors, and can become a global reference for business actors in the city of Palangka Raya. Future research can adopt research indicators to increase customer loyalty, so as to expand knowledge in the culinary business